Response of Karakoram‐Himalayan glaciers to climate variability and climatic change: A regional climate model assessment. Issue 6 (27th March 2015) - Kumar, Pankaj; Kotlarski, Sven; Moseley, Christopher; Sieck, Kevin; Frey, Holger; Stoffel, Markus; Jacob, Daniela
Abstract: The Karakoram and the Himalayan mountain range accommodate a large number of glaciers and are the major source of several perennial rivers downstream. To interactively describe to response of glaciers to climate change, a glacier parameterization scheme has been developed and implemented into the regional climate model REMO. The scheme simulates the mass balance as well as changes of the areal extent of glaciers on a subgrid scale. The parameterization scheme is for the first time applied to the region. A regional glacier inventory is compiled and is used to initialize glacier area and volume. Over the highly complex and data sparse region, the simulated mass balance largely agrees with observations including the positive Karakoram anomaly. The simulated equilibrium line altitude is well captured although a systematic underestimation is apparent. REMO simulates the glacier‐climate interaction reasonably well; it has clear potential to be used for future climate assessments. Key Points: Regional climate model coupled with dynamic glacier parameterization scheme Mass balance and ELA for Karakoram‐Himalayas glaciers